Evaluasi Pelaksanaan Program Bantuan Operasional Sekolah di Madrasah Tsanawiyah DDI Cilellang Kabupaten Barru - Kamaruddin Hasan; Andi Saharuddin (Al-Musannif, 2022)
This study aims to analyze the School Operational Assistance (BOS) program at MTs DDI Cilellang, Barru District, which focuses on implementation, evaluation, and the supporting and inhibiting factors. This type of research is descriptive qualitative. Primary data sources consist of madrasa heads, BOS treasurers, teachers, and students at MTs DDI Cilellang. Secondary data sources are in the form of relevant journals and books as a theoretical basis and BOS document data at MTs DDI Cilellang. Data was collected using observation, interview, and documentation techniques and then analyzed using descriptive analysis techniques. The results show that the implementation of the BOS program at MTs DDI Cilellang using Madrasah-Based Management (MBM) aims to empower madrasa through granting authority (autonomy). The implementation of the BOS program met a good standard based on six evaluation dimensions, namely effectiveness, efficiency, adequacy, responsiveness, equity, and accuracy. The supporting factors are good cooperation between the madrasah and the madrasah committee; expert and experienced BOS fund managers. The inhibiting factor is the delay in receiving funds from the government.